Fostering Professional Communication Competence through ESP-Based Business Document Writing among Business Management Students - Vidya Arisandi; Depi Prihamdani; Karina Chintya Lestari (Universitas Islam Negeri Palopo, 2026)
This study examines the implementation of business document writing within an English for Business Management course and its impact on the development of professional communication competencies among Business Management students. The research addresses the need for workplace-oriented English instruction that equips students to produce business documents that are clear, systematic, formal, and appropriate for professional contexts. Employing a mixed-methods approach, the study involved 120 second-semester Business Management students from four classes. Data collection methods included pretest and posttest writing tasks, a business document writing rubric, analysis of students’ written products, classroom observations, open-ended questions, questionnaires, and interviews. Quantitative data were analyzed descriptively by comparing pretest and posttest score ranges, while qualitative data were examined using thematic coding. The findings indicate that business document writing was integrated through ESP-based activities, including brainstorming, document analysis, case-based writing tasks, feedback, revision, and portfolio development. Students’ writing performance improved from a pretest score range of 40–60 to a posttest range of 69–80, with notable progress in content relevance, document structure, language use, business vocabulary, and mechanics. Qualitative results further reveal increased student awareness of key aspects of professional communication, including communicative purpose, audience awareness, document structure, formality, tone, message clarity, business vocabulary, and workplace context. The study concludes that business document writing serves as a relevant pedagogical strategy in ESP-based Business English instruction, bridging English learning with authentic workplace communication needs. However, the findings should be interpreted in context, given the descriptive nature of the quantitative data and the study’s focus on a single institutional and course setting.